Pengaruh Metode Show And Tell Terhadap Kemampuan Berbicara Siswa Di Sekolah Dasar Yayasan Sinar Husni Kota Medan - Madani, Syukur; shofa, Nurus; Wiranda, Andita; Idul, Idul; Pratiwi, Windi; Fitri, Fitri (STAI Tebing Tinggi Deli, 2024)
The process of speaking allows children to express themselves, express ideas, and state thoughts orally. However, at Sinar Husni Foundation Elementary School in Medan City, it was found that there are still students who have low participation in class discussions, they have difficulty expressing their opinions, and lack confidence when speaking in public. This indicates a problem in students' communication skills. This study aims to evaluate the effectiveness of the Show and Tell method in improving students' speaking skills. The subjects of this research are students of Sinar Husni Foundation Elementary School in Medan City. The data analysis technique uses a qualitative method with a descriptive approach. The methods used in this study include interviews, observation, and documentation. The results showed that Sinar Husni Foundation Elementary School Medan City successfully applied the Show and Tell method effectively in improving students' speaking ability. This can be seen from 1) Increased student confidence, 2) Increased students' speaking skills with clearer information delivery, and 3) Encouraging more active interaction between students, both as speakers and as listeners. From the results of the study, it can be concluded that the Show and Tell method has a positive effect on students' speaking skills at Sinar Husni Foundation Elementary School in Medan City. This method is effective in increasing students' participation in class discussions and their confidence when speaking in public.